The Soviet Union in Search of a New Economic Model - Andreas Polkowski (Intereconomics, 1987)
Seventy years after the Bolshevik Revolution the Soviet Union is to embark on a new economic path which, according to Mikhail Gorbachev, will again call for revolutionary measures. What form will these measures take? What obstacles stand in the way of the planned reforms? What are their chances of success?
Keywords: 330